2020
DOI: 10.1074/jbc.ra120.015595
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylglucosamine drives myelination by triggering oligodendrocyte precursor cell differentiation

Abstract: Myelination plays an important role in cognitive development and in demyelinating diseases like multiple sclerosis (MS), where failure of re-myelination promotes permanent neuro-axonal damage.  Modification of cell surface receptors with branched N-glycans coordinates cell growth and differentiation by controlling glycoprotein clustering, signaling and endocytosis. N-acetylglucosamine (GlcNAc) is a rate-limiting metabolite for N-glycan branching. Here we report that GlcNAc and N-glycan branching trigger oligod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 75 publications
(100 reference statements)
0
38
0
Order By: Relevance
“…Differentiation of peripheral T cells into pro-inflammatory Th1 and Th17 cells is inhibited by the galectin lattice, which combines with T cell receptor regulation, and determines the risk of autoimmune diseases such as MS (Demetriou et al, 2001;Lee et al, 2007;Grigorian et al, 2011). In addition to immune regulation, the galectin lattice drives myelination by promoting the surface retention of PDGFRα in OPC, a receptor that plays a critical role in oligodendrogenesis (Sy et al, 2020). Mgat5-mediated branching and poly-LacNAc formation depend on GlcNAc availability in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation of peripheral T cells into pro-inflammatory Th1 and Th17 cells is inhibited by the galectin lattice, which combines with T cell receptor regulation, and determines the risk of autoimmune diseases such as MS (Demetriou et al, 2001;Lee et al, 2007;Grigorian et al, 2011). In addition to immune regulation, the galectin lattice drives myelination by promoting the surface retention of PDGFRα in OPC, a receptor that plays a critical role in oligodendrogenesis (Sy et al, 2020). Mgat5-mediated branching and poly-LacNAc formation depend on GlcNAc availability in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NUCB1 was reported as a novel pan-neuronal calcium handling marker, correlated to Alzheimer’s disease [ 45 ]. Unlike those, N-acetyl-D-glucosamine has a neuroprotective role as a regulator of primary myelination and myelin repair and is of importance in demyelinating diseases like multiple sclerosis [ 46 ]. Finally, adenine is, as one of the purines, involved in neuromodulation, neurotransmission, activation of differentiation and neuritogenesis of precursor cells and neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, adenine is, as one of the purines, involved in neuromodulation, neurotransmission, activation of differentiation and neuritogenesis of precursor cells and neurons. Additionally, purines also contribute to immunological response due to astrocytes and microglia activation, initiating the inflammatory reactions [ 46 ]. The diagnostic significance and potential are yet to be examined by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, proteoglycans such as NG2 are important determinants of OPC migration [ 74 ]. Indeed, it has been reported that N-glycan branching of GlcNAc is important in myelination and myelin repair [ 75 ].…”
Section: Energy Fuels Used By Oligodendrogliamentioning
confidence: 99%